Electrochemical biosensors for monitoring of bioorganic and inorganic chemical pollutants in biological and environmental matrices - Azad U.P.; Mahapatra S.; Divya; Chandra P.; Srivastava A.; Shetti N.P. (My University, 2025)
Contamination of air and water from organic and inorganic pollutants and faster quantification of these pollutants is the key task for environmental monitoring because after entering into biological system they give birth to several severe diseases. To make onsite quantification feasible, easier, and faster analytical tools should be developed which should work with minimum sample and easy sample preparation technique. So, keeping these facts in mind, scientists from various portions of the globe have adopted numerous methodologies and used various catalytic materials to construct a senor for these pollutants. Various kinds of pollutants (inorganic and organic) and a wide range of catalytic materials used to construct electrochemical sensor, and electrochemical techniques adopted for their quantification at trace level has been individually discussed. The latest advancement in electrochemical biosensor technology in terms of fabrication and analytical performance has been discussed. Recent applications and future trends in organic and inorganic pollutants determination and electrochemical biosensor technology have also been discussed with various examples. © 2022 Elsevier Inc. All rights reserved.